Convergent Validity of the Early Memory Index in Two Primary Care Samples. Issue 3 (3rd May 2016) - Porcerelli, John H.; Cogan, Rosemary; Melchior, Katherine A.; Jasinski, Matthew J.; Richardson, Laura; Fowler, Shannon; Morris, Pierre; Murdoch, William
ABSTRACT: Karliner, Westrich, Shedler, and Mayman (1996) developed the Early Memory Index (EMI) to assess mental health, narrative coherence, and traumatic experiences in reports of early memories. We assessed the convergent validity of EMI scales with data from 103 women from an urban primary care clinic (Study 1) and data from 48 women and 24 men from a suburban primary care clinic (Study 2). Patients provided early memory narratives and completed self-report measures of psychopathology, trauma, and health care utilization. In both studies, lower scores on the Mental Health scale and higher scores on the Traumatic Experiences scale were related to higher scores on measures of psychopathology and childhood trauma. Less consistent associations were found between the Mental Health and Traumatic Experiences scores and measures of health care utilization. The Narrative Coherence scale showed inconsistent relationships across measures in both samples. In analyses assessing the overall fit between hypothesized and actual correlations between EMI scores and measures of psychopathology, severity of trauma symptoms, and health care utilization, the Mental Health scale of the EMI demonstrated stronger convergent validity than the EMI Traumatic Experiences scale. The results provide support for the convergent validity of the Mental Health scale of the EMI.